The Impact of the Risk of Losing the Betawi Language on Society - Iskandarsyah Siregar; Ahmed El Ajmi (Britain International for Academic Research (BIAR-Publisher), 2023)
The Betawi language, like many other global languages, faces the threat of extinction caused by various factors, including the evolution of civilization. This threat threatens various aspects of indigenous Betawi culture. Therefore, maintaining and preserving the Betawi language is very important. The challenge is to understand the breadth of the Betawi linguistic and textual context. It is important to develop targeted strategies that highlight the main elements affected by language degradation, especially in the Betawi community. This study identified these elements after conducting intensive field research for more than a year with continuous observations. This research shows that sociological qualitative analysis, especially in evaluating people's social interactions, is the most effective method. Five main areas were identified to analyze the impact of language decline: linguistic aspects, individual identity, intergenerational communication, knowledge transfer, and economic implications